Making community pharmacies psychologically informed environments (PIE): a feasibility study to improve engagement with people using drug services in Scotland. (16th March 2023) - Matheson, Catriona; Hunter, Carole; Schofield, Joe; O'Sullivan, Kate; Hunter, Janie; Munro, Alison; Parkes, Tessa
Abstract: Aim: This developmental study tested the feasibility of training pharmacy staff on the psychologically informed environments (PIE) approach to improve the delivery of care. Background: Community pharmacies provide key services to people who use drugs (PWUD) through needle exchange services, medication-assisted treatment and naloxone distribution. PWUD often have trauma backgrounds, and an approach that has been demonstrated to work well in the homeless sector is PIEs. Methods: Bespoke training was provided by clinical psychologists and assessed by questionnaire. Staff interviews explored changes made following PIE training to adapt the delivery of care. Changes in attitude of staff following training were assessed by questionnaire. Peer researchers interviewed patient/client on observed changes and experiences in participating pharmacies. Staff interviews were conducted six months after training to determine what changes, if any, staff had implemented. Normalisation process theory (NPT) provided a framework for assessing change. Findings: Three pharmacies (16 staff) participated. Training evaluation was positive; all participants rated training structure and delivery as 'very good' or 'excellent'. There was no statistically significant change in attitudes. COVID-19 lockdowns restricted follow-up data collection. Staff interviews revealed training had encouraged staff to reflect on their practice and communication and consider potentially discriminatory practice. PIE informed communication skills were applied to manage COVID-19 changes. Staff across pharmacies noted mental health challenges for patients. Five patients were interviewed but COVID-19 delays in data collection meant changes in delivery of care were difficult to recall. However, they did reflect on interactions with pharmacy staff generally. Across staff and patient interviews, there was possible conflation of practice changes due to COVID-19 and the training. However, the study found that training pharmacy teams in PIE was feasible, well received, and further development is recommended. There was evidence of the four NPT domains to support change (coherence, cognitive participation, collective action and reflexive monitoring).